GAMBARAN PATOLOGI HEPAR IKAN LELE DUMBO (Clarias gariepinus) YANG DIPAPAR LOGAM TIMBAL NITRAT Pb(NO3)2 - Dellavia, Yolanda; Widiyatno, Thomas Valentinus; Setiawan, Boedi; Arimbi, Arimbi; Poernomo, Bambang; Dhamayanti, Yeni (Journal of Basic Medical Veterinary, 2020)
This research aimed to know the changed damage of liver African catfish (Clarias gariepinus) were exposed by lead nitrat. This study used twenty four of African catfish (Clarias gariepinus) with average weight of 20-25 grams, size 10-12 cm, age ± two months. This research was designed by a completely randomized design (CRD). All member of population of the African catfish were divided into six groups, consist of six repetitions each, namely P1, P2, P3, and P0 as a negative control respectively.  P1 was given with dosage of lead nitrat 7,26 mg/liter, P2 was given with dosage of lead nitrat 14,53 mg/liter, and P3 was given with dosage of lead nitrat 29,06 mg/liter. According to the macroscopic observed, show that liver became swollen and pale.  The histopathological features of hepar were examined under light microscope in 400 times magnification. Scoring method were using Bernet Scoring Method to examined the presence of degeneretion, congesti, necrotic, and infiltration of leukocyte. Then, Kruskal-Wallis test through with Mann-Whitney test of statistical analysis. The statistical analysis showed the median number of P0 (0,05), P1 (0,45), P2 (1,10), and P3 (1,40) respectively. From the result can be concluded lead exposure with dose 29,06 mg/liter severe which was heavily histopatological in hepatocytes cell of african catfish (Clarias gariepinus) liver.